If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 122 + -2x = 6x + 16 Reorder the terms: 122 + -2x = 16 + 6x Solving 122 + -2x = 16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 122 + -2x + -6x = 16 + 6x + -6x Combine like terms: -2x + -6x = -8x 122 + -8x = 16 + 6x + -6x Combine like terms: 6x + -6x = 0 122 + -8x = 16 + 0 122 + -8x = 16 Add '-122' to each side of the equation. 122 + -122 + -8x = 16 + -122 Combine like terms: 122 + -122 = 0 0 + -8x = 16 + -122 -8x = 16 + -122 Combine like terms: 16 + -122 = -106 -8x = -106 Divide each side by '-8'. x = 13.25 Simplifying x = 13.25
| 3(t+2)=2-(2t-2) | | 10x-23=77 | | 2(3x+4)=2(4x+1) | | 4x^3+15x^2+37x+39=0 | | 3-2k=-9 | | 8v-10=105 | | (x+1)(x-7)=0 | | 8r^2-12r=0 | | 0=-16x^2+3x+1.3 | | 3x^2+34x+80=0 | | 18=3(d-1) | | 3-4(x+2)=15 | | x^3+x^2-x-1.7=0 | | 3a-32=-2a+23 | | 7(-6y+9)+4y=-13 | | (x*x)+(x*x)=36 | | 137-4x=23x+23 | | 20.4-2c=5 | | 4x+y+1=-y-2x+3 | | (a-b)(a^2+2ab+b^2)= | | 12y^2+2y=0 | | (2c-d)(2c^2+2cd+d^2)= | | 7-7x=29-21x | | 3x+10+x+2=2x+20 | | -3x+7=28 | | 3x-45=6 | | 7(n+6)+8(n+4)= | | 8(x+3)+14(x+2)=74 | | 3(6z-1)-4(z+9)=4(z+1) | | 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 |